Organizational Leadership Styles of Program Heads and the Performance of the Faculty of Select Higher Education Institution in Ortigas-Cainta: Basis For Organizational Leadership Enhancement Program - Jaminit, Franz (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the relationship between the organizational leadership styles of program heads and the performance of faculty members in a selected higher education institution in Ortigas-Cainta as the basis for the development of an Organizational Leadership Enhancement Program. Specifically, the study determined the demographic profile of the respondents, identified the leadership styles of program heads based on self-assessment and faculty perceptions, assessed the level of faculty performance, examined significant differences in leadership style and faculty performance across demographic variables, and determined the relationship between organizational leadership styles and faculty performance. The study employed a quantitative descriptive-correlational research design involving 102 respondents composed of five program heads and ninety-seven faculty members selected through total population sampling. Data were gathered using the adapted Leadership Style Survey by Clark (2004) and the institution’s Faculty Performance Evaluation Tool, both of which underwent validity and reliability testing prior to data collection. Statistical tools such as frequency and percentage distribution, weighted mean, t-test, one-way analysis of variance (ANOVA), and Pearson’s correlation coefficient were utilized to analyze the data at the 0.05 level of significance. Findings revealed that democratic leadership emerged as the dominant organizational leadership style based on both the program heads’ self-assessment and the faculty members’ perceptions. Faculty members rated their overall performance as Exceeds Expectations, a finding that was likewise supported by the program heads’ evaluation. The study further revealed no significant differences in leadership style based on sex and no significant differences in faculty performance when grouped according to age, sex, designation, years of experience, and employment status. However, a significant difference was found in faculty performance when grouped according to educational attainment. Moreover, the findings established a positive and significant relationship between the organizational leadership styles of program heads and faculty performance, indicating that effective leadership contributes to enhanced instructional performance and professional effectiveness. Based on these findings, an Organizational Leadership Enhancement Program was proposed to strengthen leadership competencies, sustain faculty excellence, and promote continuous professional development toward improved institutional effectiveness and educational quality.